A putative lysophosphatidylinositol receptor GPR55 modulates hippocampal synaptic plasticity. Issue 9 (27th June 2017) - Hurst, Katrina; Badgley, Corinne; Ellsworth, Tanner; Bell, Spencer; Friend, Lindsey; Prince, Brad; Welch, Jacob; Cowan, Zack; Williamson, Ryan; Lyon, Chris; Anderson, Brandon; Poole, Brian; et al.
Abstract: GPR55, an orphan G‐protein coupled receptor, is activated by lysophosphatidylinositol (LPI) and the endocannabinoid anandamide, as well as by other compounds including THC. LPI is a potent endogenous ligand of GPR55 and neither GPR55 nor LPIs' functions in the brain are well understood. While endocannabinoids are well known to modulate brain synaptic plasticity, the potential role LPI could have on brain plasticity has never been demonstrated. Therefore, we examined not only GPR55 expression, but also the role its endogenous ligand could play in long‐term potentiation, a common form of synaptic plasticity. Using quantitative RT‐PCR, electrophysiology, and behavioral assays, we examined hippocampal GPR55 expression and function. qRT‐PCR results indicate that GPR55 is expressed in hippocampi of both rats and mice. Immunohistochemistry and single cell PCR demonstrates GPR55 protein in pyramidal cells of CA1 and CA3 layers in the hippocampus. Application of the GPR55 endogenous agonist LPI to hippocampal slices of GPR55 +/+ mice significantly enhanced CA1 LTP. This effect was absent in GPR55 −/− mice, and blocked by the GPR55 antagonist CID 16020046. We also examined paired‐pulse ratios of GPR55 −/− and GPR55 +/+ mice with or without LPI and noted significant enhancement in paired‐pulse ratios by LPI in GPR55 +/+ mice. Behaviorally, GPR55 −/− and GPR55 +/+ mice did not differ in memory tasks including novel object recognition, radial arm maze, or Morris water maze. However, performance on radial arm maze and elevated plus maze task suggests GPR55 −/− mice have a higher frequency of immobile behavior. This is the first demonstration of LPI involvement in hippocampal synaptic plasticity.